Heat stress affects tassel development and reduces the kernel number of summer maize - Liu, Pan; Yin, Baozhong; Gu, Limin; Zhang, Shaoyun; Ren, Jianhong; Wang, Yandong; Duan, Weiwei; Zhen, Wenchao (Frontiers in Plant Science, 2023)
The grain yield of maize is drastically reduced by heat stress during flowering and early grain filling. Yet, the mechanism of high temperature stress (HTS) on maize reproductive organs and the number of kernels per ear remains poorly known. During 2018–2020, two maize varieties (ND372, a heat-tolerant variety, and XY335, a heat-sensitive variety) and two temperature approaches (HTS, high temperature stress, and CK, natural control) formed four treatments (372CK, 372HTSS, 335CK, and 335HTS), with HTS conducted from the 9th leaf stage to the powder dispersal stage. Various morphological traits and physiological activities were assessed in the tassel, anther, and pollen of various maize types to determine their correlation with kernel number per ear. Results showed that the number of florets, tassel volume, and tassel length were all reduced by HTS, although the maximum number of tassel branches was enhanced. Moreover, HTS accelerated tassel degradation. HTS reduced pollen weight, pollen quantity, and pollen activity. Deformation and a reduction in length and volume due to HTS were observed in both the ND372 and XY335, with average reductions of 22.9% and 35.2%, respectively. The morphology of the anther changes more noticeably in heat-sensitive maize. HTS dramatically reduced maize kernels per spike compared to CK, with ND372 and XY335 showing decreases of 47.3% and 59.3%, respectively. The main factors for the decrease kernel number maize due to high temperature were the reduction in pollen amount and weight, tassel spindle and branch length. High temperature had a greater impact on heat-sensitive maize's anther shape, pollen viability, and phenotypic than that on non-sensitive varieties. High temperature had a greater impact on heat-sensitive maize's anther morphology, pollen viability, and phenotypic, but it had no influence on the appearance or dissemination of pollen in male maize ears.